1993
DOI: 10.1159/000236516
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Latex Allergy in Atopic Children and Hospital Workers in Japan

Abstract: The incidence of latex-induced allergy has been reported to be increasing in Europe and the US but not in Japan. We thus measured latex-specific IgE antibodies and latex-specific IgG antibodies in sera from 196 atopic children with low serum IgE levels (under 1,000 U/ml; group 1), 108 atopic children with high serum IgE levels (over 1,000 U/ml; group 2) and 601 hospital employees (group 3). Atopic children were diagnosed as having asthma, atopic dermatitis and/or food intolerance. One out of group 1 (0.5%) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 6 publications
0
9
0
Order By: Relevance
“…Akasawa et al (15) found latex‐specific IgE in 10.2% atopic children (11/108) with total serum IgE higher than 1000 kU/l and in 0.5% (1/196) of children with total serum IgE of less than 1000 kU/l. In this study, a concordance between latex‐specific skin prick tests and IgE was found in 7 out of 12 sensitized children whereas in the present study only 3 out of 22 children with positive specific IgE also had positive skin prick tests to latex.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Akasawa et al (15) found latex‐specific IgE in 10.2% atopic children (11/108) with total serum IgE higher than 1000 kU/l and in 0.5% (1/196) of children with total serum IgE of less than 1000 kU/l. In this study, a concordance between latex‐specific skin prick tests and IgE was found in 7 out of 12 sensitized children whereas in the present study only 3 out of 22 children with positive specific IgE also had positive skin prick tests to latex.…”
Section: Discussionmentioning
confidence: 99%
“…Various prevalence studies in children not belonging to the surgical risk group have been carried out in several countries, although using different populations (atopic children, non-atopic children, schoolchildren and allergy clinic children; different age groups) as well as different diagnostic methods (questionnaires, skin prick tests and specific IgE). However, the prevalence of latex allergy in children without surgical risk is low, although it seems to be higher in children with previous atopy (14)(15)(16)(17)(18)(19)(20)(21)(22).…”
mentioning
confidence: 99%
“…IgE-mediated hypersensitivity to latex proteins is an increasing problem, especially among medical personnel, who frequently wear latex gloves (16)(17)(18)(19)(20)(21), as well as in patients with congenital malformations (22-24). In the general population, the prevalence of sensitization to latex proteins was estimated to be around 3.5% (25).…”
Section: Discussionmentioning
confidence: 99%
“…Natural latex is known to contain multiple allergenic proteins in the range 5-100 kDa (16,(33)(34)(35)(36)(37)(38). Rubber elongation factor, hevein and prohevein are known to be major allergens (35,36,39).…”
Section: Discussionmentioning
confidence: 99%
“…Skin prick test reactions and/or specific serum IgE antibodies to NRL without indications of a clinically relevant allergy were found in 121 subjects (24.5%); 97 (80.2%) of these were rated atopic. Other investigators also found that reactions to NRL in the skin prick test (2,18) or NRLspecific serum IgE antibodies (24,25) without a concordant history are seen mainly in atopies. Without a history of NRL allergy and without intense NRL exposure, from 3.75% (18) to 5.0% (2) of atopic subjects exhibit reactions at NRL skin prick testing.…”
Section: Discussionmentioning
confidence: 93%